(untitled) - Meyers, Gerald C. (Boston, 1986)
Former American Motors chairman Meyers, a visiting professor at the Carnegie-Mellon business school, and Holusha, Detroit bureau chief of the New York Times, outline fateful stages in a corporate business crisis: gradual failure (of product, management or market), denial and recrimination, anger and fear, panic and collapse. The pattern in recent years is oft-repeatedContinental Illinois, Schlitz, Union Carbide, Braniff Air, to name a few. But crises can be managed, stress the authors, and, if overcome, can give a corporation new life and create new business heroes (e.g., Lee Iacocca's last-minute crisis management at Chrysler). Meyers and Holusha provide an absorbing look at the dark side of American business along with a generous bundle of object lessons for turning things around.
Keywords: Crisis management